DEVELOPING STUDENT’S ASSESSMENT OF WRITING RECOUNT TEXT BASED ON PROJECT ASSESSMENT FOR TENTH GRADE AT SMK NEGERI 2 BINJAI - Nora Humairoh; Rahmad Husein; Fahri Haswani (Universitas Negeri Medan, 2020)
The objective of the study is to develop project assessment for student’s writing assessment of recount text and to design the appropriate assessment for Computer Network Enginering students grade X at SMK Negeri 2 Binjai. It used qualitative research method to collect and analyze the teacher’s authentic assessment. The data of the study were taken from English teacher of Computer Network Engineering grade X at SMK Negeri 2 Binjai. The findings showed from the existing assessment analysis, interview analysis, and questionnaires analysis. The average of the project assessment is 4,6 and the percentage is 92% The result showed that the development of project assessment at SMK Negeri 2 Binjai is categorized in “Very Good”, category. It showed that the development of project assessment categorized “Very Good” due to some obstacle and supporting factors. Project assessment development already measured the all aspects of writing skill. Keywords: Project assessment, development, writing, Computer Network Engineering.